A rare cause of acute ST-elevation myocardial infarction: a case of coronary embolism secondary to calcified bicuspid aortic valve - Anda Bularga; Andrew R Chapman; John Hung; Nicholas L. Mills; Marc R. Dweck (Sciendo, 2021)
Coronary embolism is an uncommon cause of acute myocardial infarction, which can have a similar clinical presentation to a plaque rupture event with acute onset of ischaemic symptoms, ST segment elevation on electrocardiogram (ECG) and significant elevation in cardiac troponin, requiring immediate intervention. We report the case of a middle-aged female with a background history of previous non-ST elevation myocardial infarction, bicuspid aortic valve with severe stenosis and metastatic breast cancer. The patient underwent emergency coronary angiography following acute onset central chest pain and evidence of anterior ST segment elevation on ambulance 12-lead ECG. The procedure revealed complete occlusion of the mid left anterior descending coronary artery with immediate fl ow restoration following embolus aspiration and subsequent normal appearance of the left anterior descending coronary artery. Gross examination of the aspirated specimen resembled a calcified hard lump, which was further confirmed on microscopic examination revealing calcified fibrous tissue most likely an embolus from the calcified bicuspid aortic valve. The patient had evidence of near transmural myocardial infarction in the distribution of the left anterior descending coronary on cardiac magnetic resonance imaging (MRI). She made full recovery and was discharged on short-term dual antiplatelet therapy followed by lifelong aspirin and further assessment for aortic stenosis management.